1993
DOI: 10.1111/j.1360-0443.1993.tb02021.x
|View full text |Cite
|
Sign up to set email alerts
|

HIV risk among women injecting drug users who are in jail

Abstract: Female offender populations and females in jail include large proportions of injecting drug users (IDUs), who are at high risk of contracting or transmitting HIV. Women IDUs (n = 165) were recruited and interviewed at New York City's central jail facility for women. The study examined these women's patterns of HIV risk behaviors related to drugs and sex and identified behavioral and attitudinal correlates of HIV serostatus. The women typically used both injectable and non-injectable drugs prior to arrest, prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
29
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 25 publications
2
29
0
Order By: Relevance
“…[19][20][21][22][23][23][24][25] Addictions to drugs and alcohol have been identified as key variables in the propagation of such risks, and an array of prison-based and postincarceration intervention models have been developed and are being evaluated. 19,[26][27][28] It is crucial to determine ways to reduce HIV risk behaviors among incarcerated women returning to the community. Lower educational attainment has been reported as a risk factor for higher rates of HIV risk behavior among female inmates, although evaluation of different educational factors has not been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23][23][24][25] Addictions to drugs and alcohol have been identified as key variables in the propagation of such risks, and an array of prison-based and postincarceration intervention models have been developed and are being evaluated. 19,[26][27][28] It is crucial to determine ways to reduce HIV risk behaviors among incarcerated women returning to the community. Lower educational attainment has been reported as a risk factor for higher rates of HIV risk behavior among female inmates, although evaluation of different educational factors has not been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Later studies, however, suggested that female and male IDU engaged in injection risk behavior differently (Bennett et al, 2000;Dwyer et al, 1994;Gollub et al, 1998;Miller and Neaigus, 2001) and that risk factors for HIV infection among IDU differed between the sexes (Bruneau et al, 2001;Kral et al, 1997;Strathdee et al, 2001;van Ameijden et al, 1999). Studies reporting exclusively on HIV transmission in female IDU detected additional risk among women of color (Magura et al, 1993;Watters et al, 1994), women who engaged in prostitution (Astemborski et al, 1994;Watters et al, 1994), who were out of drug treatment (Bruneau et al, 2001), and who had a history of sexually transmitted disease Watters et al, 1994). However, far less is known about the determinants of HIV-related risk behavior among female injectors since the establishment in the U.S. of syringe exchange programs (SEPs).…”
Section: Introductionmentioning
confidence: 99%
“…Women involved in the criminal justice system are likely to be at higher risk for cervical cancer because of a history of multiple sex partners, 26 early parity, trading sex for money or drugs, 27,28 and tobacco use. We designed this study to compare the prevalence of reported abnormal Pap tests in women involved with the criminal justice system in jail and in the community in two Southern cities.…”
Section: Introductionmentioning
confidence: 99%